Protective and Ameliorative Effect of The Tinospora cordifolia Extract Against Cisplatin Effect on Sperm Parameters of Males Rats (Journal of Pharmaceutical Negative Results, 2022)
Infertility is the biggest problem be facing doctors for treating the patients that undergo the different types of cancer disease. Since the chemotherapies drugs have an adverse effect on the testis tissue and, therefore, sperm quality. Cisplatin is used one of the most potent and widely used for treating ovarian cancer, lung carcinoma, and lymphoma. Cisplatin causes testicular degeneration and decreases sperm quality. Natural antioxidants drove from plants and fruits reduce the negative impact and have productive properties against anticancer drugs. Tinospora cordifolia is a medicinal herb from India used as a potential natural complementary treatment for specific health conditions, which is used as an immunity improved, anti-inflammatory, antioxidant and anticancer. Thus, this study aimed to evaluate the protective and ameliorative effect of the Tinospora cordifolia against adverse cisplatin on reproductive parameters. In this study, 40 healthy adult male rats were used in four groups control, cisplatin-induction, and two deferent concentration of aqueous extract of Tinospora cordifolia. The result showed an improvement effect of aqueous extract of Tinospora cordifolia administered by gavage at 200 mg/kg concentration against Cisplatin.